Case of small bowel perforation secondary to nivolumab and ipilimumab related tumour regression - Patel, Kishen Rajan (BMJ Case Rep, 2020)
A 56-year-old man undergoing immunotherapy treatment for metastatic melanoma presented with sudden onset testicular pain radiating into his abdomen. On examination, the abdomen was generally tender with associated guarding. Imaging revealed a perforation of the small bowel at the site of a metastatic lesion. Histology revealed that this process was non-inflammatory in nature. A diagnosis of small bowel perforation secondary to immunotherapy driven rapid tumour regression was made. The patient was treated with a small bowel resection plus anastomosis and made a full recovery. This case highlights the rare potential side effect of immunotherapy in causing non-inflammatory bowel perforations secondary to rapid tumour regression.